Analysis Of The Influence of Organizational Culture, Work Discipline, And Job Satisfaction On Employee Performance At Pt. Bank Syariah Indonesia Office Area Semarang City - Mardhotillah, Mai'syah; Hasanah, Siti; Ulya, Nur Maziyah (ITB AAS INDONESIA Surakarta, 2024)
This study aims to analyze the significant effect of Organizational Culture, Work Discipline, and Job Satisfaction on Employee Work Productivity with Work Motivation as a Moderating Variable at Bank Syariah Indonesia Branch Office of the Student Army Soldiers in Semarang City, either simultaneously or partially. The population in this study were all employees of Bank Syariah Indonesia Semarang City Area Office, while the sample in this study were 34 respondents who became employees of Bank Syariah Indonesia Semarang City Area Office who were selected using a saturated sampling technique. The data used in this study are primary data obtained through distributing questionnaires. The analysis model used in this study was the Multiple Linear Regression Analysis Model, while the data analysis technique used a simultaneous significance test (F test), coefficient of determination test (R2), and partial significance test (t-test) which were processed with the SPSS 25.00 program. The results of proving the hypothesis and discussion show that the variables of organizational culture, work discipline, and job satisfaction simultaneously have a significant effect on employee performance at PT Bank Syariah Indonesia Semarang City Area Office. Partially, the organizational culture and work discipline variables each have a positive and significant effect, while the job satisfaction variable partially has a positive but not significant effect on employee performance at PT Bank Syariah Indonesia Semarang City Area Office. Keywords: Employee Performance, Organizational Culture, Work Discipline, Job Satisfaction